The Relationship Between Sex and Age with the Suspected Incidence of Malaria Based on Rapid Diagnostic Test (RDT) Results in the Working Area of the Tanjung Leidong Health Centre, North Labuhanbatu District in 2023 - Maharani, Safira Adelia; Handayani, Dewi Yanti; Damanik, Rosa Zorayatamin; Ismail, Wan Muhammad (International Journal of Public Health Excellence (IJPHE), 2025)
Background: Malaria is a global problem and it’s incidence increasing every year. Malaria caused by several factors such as gender and age. Men are more at risk of malaria than woman and adults are more affected by malaria than children and the elderly. Methods: This study used observational analysis method with Cross-Sectional approach with total sampling technique, with 754 samples that fit the inclusion criteria. The data was analized with Chi-square test correlation analysis, and Risk metode to determine the Prevelence ratio value, and also the contingency coefficient test. Results: The most positive RDT results were found in men (62.4%) and (53.1%) were found in adult with the results of the chi-square test on the gender variable and RDT results obtained a value of p-value = 0.00 (p < 0.05) and OR = 14.9 (CI 95% 5,845-38,032) which means there is a relationship between gender and the incidence of malaria and men have a high risk of malaria 14.9 times greater than women. The results of the age variable test with the incidence of malaria using Coefficient Contingency with Spearman Correlation obtained a value of p = 0.000 (p <0.05) with an r-value = 0.194. These results indicate that there is a relationship between age and malaria incidence rates with a very weak correlation value. Discussion: man and adults are more affected by malaria due to outdoor physical activity, immune system influences, and hormonal system influences. Adults are more often affected by malaria due to lifestyle and daily activities.